Chapter Looking at China's cultural complexity. Food, colours and ritual: sensuous epistemology and the construction of identity in the "other" China - Turini, Cristiana (Studi e saggi, 2021)
Studies on ethnic and cultural diversity within China have progressively eroded the far too simplistic and widespread idea of ​​the Chinese nation as a monolith. In the resulting multicultural internal context, food is definitely more than a necessity for survival and can signify the desire of a community to stabilize a fluid and multiple identity. At the same time, it can be seen also as an indication of the multitude of relationships that the individual forms not only with others as individuals, but even as spirits, gods, and demons. The aim of this contribution is to explore some of the complexity of foodways involving consumption and religion and to understand the extent to which religious uses of foods contribute to the forging and transmission of cultural identity. I will do this by referring to the Naxi people of the Lijiang area as my case-study. My analysis will also take into account how, through the exploration of the Naxi religious foodways and cosmology, it is possible to gain an insight into their culturally different balances of the senses and their sensuous epistemology. This study will be based mainly on Naxi ritual manuscripts and videos of ceremonies, collected and made during my fieldwork in Yunnan.